ACCUMULATION OF LEAD AND CADMIUM IN TISSUES OF CYPRINUS CARPIO COLLECTED FROM CAGES OF AL-GHARRAF RIVER /THI QAR / IRAQ - Al-Aboudi, H. J.; Al-Rudainy, A. J.; Maktoof, A. Abid Maktoof (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the lead and cadmium in water and in fish samples collected from three sites of Gharraf River at Thi Qar from September 2020 until April 2021. Results showed that (Pb) in river water ranged 0.156 - 4.306µg/l and the (Cd) 0.074 - 0.523 µg/l which recorded a significant differences among all sites as well as among all seasons. In addition the concentrations of Pb in some tissues of Cyprinus carpio ranged 0.069 - 4.98µg/g in muscles and kidney respectively, while Cd ranged 0.038 - 1.46 µg/g in muscles and kidney respectively. The study also showed a significant differences in Pb concentrations in fish tissues among all sites during seasons and recorded a significant differences in the summer compared with other season for Pb and Cd. A significant difference was also found in Pb and Cd concentrations between cages fish and the wild fishes for all seasons. The study proved that the water of the Al-Gharraf River is of low toxicity and less than the Iraqi and international standards, and the accumulation of Pb and Cd in the muscles of fish was less than the limits of the Federal Agency for Environmental Protection and the World Health Organization.